Distinct Impact of Processing on Cross-Order Cry1I Insecticidal Activity - Dafne Toledo; Yolanda Bel; Stefanie Menezes de Moura; Juan Luis Jurat-Fuentes; Maria Fatima Grossi de Sa; Aida Robles-Fort; Baltasar Escriche (Toxins)
The insecticidal Cry proteins from Bacillus thuringiensis are used in biopesticides or transgenic crops for pest control. The Cry1I protein family has unique characteristics of being produced during the vegetative rather than sporulation phase, its protoxins forming dimers in solution, and exhibiting dual toxicity against lepidopteran and coleopteran pests. The Cry1Ia protoxin undergoes sequential proteolysis from the N- and C-terminal ends, producing intermediate forms with insecticidal activity, while in some cases, the fully processed toxin is inactive. We investigated the oligomerization and toxicity of Cry1Ia intermediate forms generated through trypsinization (T-Int) and larval gut fluid (GF-Int) treatments, as well as the fully trypsinized protein (toxin). Heterologously expressed intermediate forms assembled into oligomers and showed similar toxicity to Cry1Ia protoxin against Ostrinia nubilalis (European corn borer) larvae, while the toxin form was ~30 times less toxic. In contrast, bioassays with Leptinotarsa decemlineata (Colorado potato beetle) larvae did not show significant differences in toxicity among Cry1Ia protoxin, T-Int, GF-Int, and fully processed toxin. These results suggest that the Cry1I mode of action differs by insect order, with N-terminal cleavage affecting toxicity against lepidopteran but not coleopteran larvae. This knowledge is essential for designing pest control strategies using Cry1I insecticidal proteins.